Perceived Parenting Styles on Emotional Regulation and Social Anxiety among Young Adults - Srikari Cheruvu; Deepthi D P (International Journal of Indian Psychȯlogy, 2022)
This study investigates the relationship between perceived parenting styles, emotional regulation, and social anxiety among young adults. The combination of perceived parenting styles, emotional regulation, and social anxiety can have a significant impact on an individual’s behavior, affecting their ability to form relationships, engage in healthy behaviors, and function in their daily lives. This study included young adults who are living under single or both parents and are unmarried. A non-probability purposive sampling method was used to draw a sample of 229 respondents from Bengaluru, India. Pearson’s Correlation, Independent sample t-test and Multiple Linear Regression were used to analyze the data. The results of the study showed that authoritarian and permissive parenting styles were positively associated with social anxiety, while authoritative parenting was negatively associated with social anxiety. Emotional regulation partially mediated the relationship between parenting styles and social anxiety. The study also found significant differences in perceived parenting styles between young adults in different age groups. Overall, the study highlights the importance of parenting styles and emotional regulation in the development of social anxiety among young adults. This study can be further used to incorporate objective measures, such as physiological measures or behavioral observations, to provide a more comprehensive understanding of the relationship between these variables.